Electron−phonon interactions in Ce3+-doped yttrium aluminum garnet nanophosphors - Su, Liap Tat (2011)
Ce3+-doped yttrium aluminum garnet nanophosphors with sizes near 30 and 250 nm have been synthesized by using chemical gelation and solvothermal methods, respectively. The size-dependent electron-longitudinal-optical-phonon coupling is investigated by fitting measured photoluminescence spectra within the framework of the Brownian oscillator model. Results show that the coupling strength is in a decreasing order from the bulk material to the nanophosphors of much smaller sizes.